2004
DOI: 10.1002/anie.200353787
|View full text |Cite
|
Sign up to set email alerts
|

Arylzinc Complexes as New Initiator Systems for the Production of Isobutene Copolymers with High Isoprene Content

Abstract: The initiator system [Zn(C6F5)2]/tBuCl for isobutene/isoprene copolymerizations (see scheme) gave products with high molecular weights, significantly increased isoprene incorporation, and minimal cross-linking

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 54 publications
1
25
0
Order By: Relevance
“…2 mol‐% IP incorporation was obtained for this initiator system. Zinc‐based initiators are evidently less affected by higher IP concentrations than Et 2 AlCl/ t BuCl for example; indeed we have shown earlier that another zinc initiator, Zn(C 6 F 5 ) 2 (toluene)/ t BuCl, is capable of producing high molecular weight linear copolymers with nearly 15 mol‐% IP 24…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…2 mol‐% IP incorporation was obtained for this initiator system. Zinc‐based initiators are evidently less affected by higher IP concentrations than Et 2 AlCl/ t BuCl for example; indeed we have shown earlier that another zinc initiator, Zn(C 6 F 5 ) 2 (toluene)/ t BuCl, is capable of producing high molecular weight linear copolymers with nearly 15 mol‐% IP 24…”
Section: Resultsmentioning
confidence: 81%
“…We have recently reported zinc‐based initiator systems for isobutene (IB) polymerizations and shown that mixtures of Zn(C 6 F 5 ) 2 (toluene) and alkyl halides give isoprene (IP)‐rich high molecular weight IB copolymers at −78 to −35 °C 24. Another zinc initiator, EtZnCl/ t BuCl, homopolymerizes IB at room temperature to give the so‐called ‘highly reactive’ PIBs with $\overline M _{\rm n}$ values of 10 000–28 000 g · mol −1 and up to 92% terminal CC bonds 25.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the low‐level unsaturated units between long polyisobutylene segments will bring about the excellent gas barrier and good flex properties of BIIR . However, only a few experimental studies on altering the copolymer composition of IIR rather than BIIR have been reported . For example, Garratt et al developed an initiating system for preparing IIR with high isoprene content and confirmed the high efficiency of the system .…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few experimental studies on altering the copolymer composition of IIR rather than BIIR have been reported . For example, Garratt et al developed an initiating system for preparing IIR with high isoprene content and confirmed the high efficiency of the system . McInenly et al successfully prepared a high isoprene content IIR and found that the T g increased with increasing isoprene content .…”
Section: Introductionmentioning
confidence: 99%
“…The saturated hydrocarbon backbone is responsible for many advantageous properties of PIB, but it also limits the ability to modify and tune the properties of the polymer. Thus, many applications of PIB have involved the introduction of chemical functionalities to the PIB backbone or termini, or the incorporation of PIB into block copolymers . For example, IB can be copolymerized with small amounts (i.e.…”
Section: Introductionmentioning
confidence: 99%